Lee De Forest papers - De Forest, Lee, 1873-1961.
Correspondence, diaries (1891-1949; 23 volumes), technical notes, manuscripts of essays and poetry, biographical sketches, clippings, printed material, memorabilia, schematics, sketches, and photographs relating to De Forest's inventions in radio and electronics and their effect on sound recording and transmission, efforts to exploit his discoveries through various business ventures, and his competition with marchese Guglielmo Marconi in the field of wireless communication. Also includes material concerning his activities as a student in preparatory school and at Yale University.
Microfilm edition of diaries available
Microfilm produced from originals in the Manuscript Division.
Radio pioneer and inventor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Marconi, Guglielmo, -- marchese, -- 1874-1937.; Yale University -- Students; Electronics; Inventions; Preparatory schools; Radio; Sound -- Recording and reproducing; Sound -- Transmission; Wireless communication systems; Inventors; Radio pioneers